Time to initiation of antiretroviral therapy in HIV‐infected patients diagnosed with an opportunistic disease: a cohort study. Issue 4 (18th December 2014) - Deconinck, L; Yazdanpanah, Y; Gilson, RJ; Melliez, H; Viget, N; Joly, V; Sabin, CA
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to identify factors associated with the time between opportunistic disease (OD) diagnosis and antiretroviral therapy (ART) initiation in HIV‐infected patients presenting for care with an OD, and to evaluate the outcomes associated with any delay. Methods A multicentre cohort study was undertaken in London, Paris and Lille/Tourcoing. The medical records of patients diagnosed from 2002 to 2012 were reviewed. Results A total of 437 patients were enrolled in the study: 70% were male, the median age was 40 years, 42% were from sub‐Saharan Africa, 68% were heterosexual, the median CD4 count was 40 cells/μL, and the most common ODs were Pneumocystis pneumonia (37%), tuberculosis (24%), toxoplasmosis (12%) and Kaposi's sarcoma (11%). Of these patients, 400 (92%) started ART within 24 weeks after HIV diagnosis, with a median time from OD diagnosis to ART initiation of 30 [interquartile range (IQR) 16–58] days. Patients diagnosed between 2009 and 2012 had a shorter time to ART initiation than those diagnosed in earlier years [hazard ratio (HR) 2.07; 95% confidence interval (CI) 1.58–2.72]. Factors associated with a longer time to ART initiation were a CD4 count ≥ 200 cells/μL (HR 0.30; 95% CI 0.20–0.44), tuberculosis (HR 0.40; 95% CI 0.30–0.55) and diagnosis in London (HR 0.62; 95% CI 0.48–0.80). Patients initiating 'deferred' ART (by ≥ 30 days) exhibited no difference in disease progression or immunovirological response compared with patients who had shorter times to ART initiation. Patients in the 'deferred' group were less likely to have ART modifications (HR 0.69; 95% CI 0.48–1.00) and had shorter in‐patient stays (mean 14.2 days shorter; 95% CI 8.9–19.5 days) than patients in the group whose ART was not deferred. Conclusions The time between OD diagnosis and ART initiation remains heterogeneous and relatively long, particularly in individuals with a high CD4 count or tuberculosis or those diagnosed in London. Deferring ART was associated with fewer ART modifications and shorter in‐patient stays.